(3GdQbGHI GdbVGFjI Ydi OSJhQjI GdbhGfjf ai Ohd eLdS GdJYGhf (B: s (3OQGSI ebGQfI (B/ s - (3eHGQc fGUQ GdgGLQis; (3jMji YHOGdYRjR GdLeds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3jeKd GdGdJRGe HeHOG GdTQjYI hGdNVhY dg gOaG GSGSjG JSYi GdjI GdGfXeI GdbGfhfjI GdeNJdaI ShGA GfJgLJ GdePgH GddjHjQGdi Ge GdePgH GdJOGNdi fXQG deG jeKdI JMbjb gPG GdgOa ef GXgGQ GdhLg GdeJMVQ ddOhdI Ydi GdeSJhjjf GdOGNdi hGdNGQLi hJYejb GdMjGI GdOjebQGWjI ajgG aGdTQYjI GdbGfhfjI JVef JhRjY hXGFa GdOhdI Hjf gjFGJ hGLgRI eNJdag heJfhYI Hjf JTQjYjI hJfajPjI hbVGFjI ef LGfH hNVhY gPI GdGLgRI hGdgjFGJ dMOhO gPI GdTQjYI ef LGfH GNQs
(3jTJed Ydi edGMb(B: (3UaMI (B625-656s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2008s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B657-690s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdOSJhQs; (3GdQbGHI GdbVGFjIs; (3GdeMceI GdOSJhQjI GdYdjGs; (3eMGce GdGSJfFGas; (3JTcjd GdeMceI GdYdjGs; (3GdQbGHI GdbVGFjI aj bWQs; (3GdQbGHI GdbVGFjI Ydj OSJhQjI GdbhGfjfs; (3eYfj GdOSJhQjs; (3dGeQcRjI GdQbGHIs; (3WQjb GdOaY GdaQYjs; (3fXGe GdOaY GdaQYjs; (3WQb GdGMGdI hGdJUOjs; (3GdOaY HYOe GdOSJhQjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes